So-Cheong-Ryoung-Tang Attenuates Pulmonary Inflammation Induced by Cigarette Smoke in Bronchial Epithelial Cells and Experimental Mice - Na-Rae Shin; Chul Kim; Chang-Seob Seo; Je-Won Ko; Young-Kwon Cho; Jong-Choon Kim; Joong-Sun Kim; In-Sik Shin (Frontiers Media S.A., 2018)
So-Cheong-Ryoung-Tang is a traditionally used herbal formula for the treatment of pulmonary diseases in China, Korea, and Japan. We investigated the protective effects of So-Cheong-Ryong-Tang water extract (SCWE) in cigarette smoke concentrate (CSC) stimulated human airway epithelial cell line NCI-H292 and mice exposed cigarette smoke (CS) and lipopolysaccharide (LPS). In the CSC-stimulated NCI-H292 cells, SCWE inhibited proinflammatory cytokines in a concentration-dependent manner, as evidenced by a reduction in their mRNA levels. Also, SCWE significant reduced inducible nitric oxide synthase (iNOS) expression and nuclear factor kappa B (NF-κB) phosphorylation in CSC-stimulated cells. The mice were exposed to CS for 1 h per day (a total of eight cigarettes per day) for 7 days and received LPS intranasally on day 5. The mice were administered a dose of SCWE (100 and 200 mg/kg) 1 h before CS exposure. In in vivo, SCWE decreased the inflammatory cell count and reduced the expression of the proinflammatory cytokines in the broncho-alveolar lavage fluid (BALF) compared with CS and LPS exposed mice. SCWE attenuated inflammatory cell infiltration in airway induced by CS and LPS exposure, and this decrease was accompanied by a reduction in the expression levels of iNOS and MMP-9 in lung tissue. The extract also inhibited the phosphorylation of inhibitor of kappa B alpha (IκBα) and NF-κB induced by CS and LPS exposure in lung tissue. These results suggest that SCWE may effectively inhibit airway inflammatory responses induced by CS and LPS exposure via the NF-κB pathway. Therefore, SCWE may be a potential treatment for airway inflammatory diseases, such as chronic obstructive pulmonary disease (COPD).